2019
DOI: 10.1109/tia.2019.2914193
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Review of the Resonant Gate Driver in the Silicon MOSFET and the GaN Transistor Application

Abstract: The increasing transistor power loss brought by the high switching frequency places a limit to the future high power density converter design. A review of resonant gate drivers is given in this paper to provide a vision for its future application. Various resonant gate driver topologies from the prior-art research is categorized and thoroughly compared in terms of the implementation frequency and the percentage gate driver loss reduction. Moreover, a case study of two representative resonant gate driver topolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Table 38 categorizes the reviewed papers according to whether they adopted commercial drivers or self-designed drivers and whether the designed circuits are single-channel or dual-channel circuits, and adopted deriver ICs (if used) are also listed. Sun et al [ 57 ] compared resonant gate drivers for both Si MOSFETs and GaN HEMTs applications. It was concluded that the resonant driver reduced switching losses because of fast charging/discharging capability.…”
Section: Review On Gan Hemt Driving Circuitsmentioning
confidence: 99%
“…Table 38 categorizes the reviewed papers according to whether they adopted commercial drivers or self-designed drivers and whether the designed circuits are single-channel or dual-channel circuits, and adopted deriver ICs (if used) are also listed. Sun et al [ 57 ] compared resonant gate drivers for both Si MOSFETs and GaN HEMTs applications. It was concluded that the resonant driver reduced switching losses because of fast charging/discharging capability.…”
Section: Review On Gan Hemt Driving Circuitsmentioning
confidence: 99%
“…Step-up moed Introducing ( 8) into ( 4) and ( 5), the averaged equations of inductor voltage in step-up mode is given (11) iC2 equals the difference between the RMS value of the load current and iL, which can be expressed by (12) Therefore, both modes have the same averaged equation of output capacitor current, which is given in (13). (13) Consequently, both operating modes of the converter have the same averaged state equations.…”
Section: B Step-up Operating Modementioning
confidence: 99%
“…On the other hand, high switching frequency also offers the possibility of increasing the power density due to the reduced size of passive components. Compared to Silicon (Si) MOSFET, wide bandgap (WBG) devices have smaller onresistance, lower parasitic capacitance and higher operating temperature, thereby are considered as the promising candidates for high frequency power conversion applications [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency mixer [1][2][3] is instrumental in a wireless communication system. By utilizing the nonlinear characteristic of components such as the diode or transistor [4,5], the electrical circuit produces new signals at the sum and difference of the original frequencies. Increasing types of frequency mixers such as passive mixers and active mixers are present in almost every wireless communication electronics system; however, the frequency mixer for a spatially propagating EM wave, with tantalizing applications in new architecture wireless communication systems [6][7][8], is more elusive.…”
Section: Introductionmentioning
confidence: 99%